The level of Malay awareness towards unit trust investment / Ku Nur Awatif Ku Ibrahim Najib - Ku Ibrahim Najib, Ku Nur Awatif (Faculty of Business and Management, 2011)
This study is to investigate the level of Malay awareness towards unit trust investment. The objective of this research is to identify the level of Malay awareness towards unit trust investment. Second objectives is to examine whether benefits influence the awareness in unit trust and the next objectives is to examine whether benefits influence the awareness in unit trust investment. A fourth objective is to investigate whether risks influence the awareness in unit trust investment. A last objective is to study whether return influence the awareness in unit trust investment. In this study, 100 questionnaires were distributed conveniently to respondent in Keramat, Setiawangsa, Damai and Wangsa Maju. This research will only focus on Malay respondents. This questionnaire will be distributed by researcher personally. The research is using simple random sampling technique, where it will be distribute randomly to the respondents. The relationship between the independent and dependent variable will be testing using Pearson Correlation. Then, researcher carried out analysis which contains of Pearson Correlation Coefficient, Reliability Analysis, Frequency Analysis, Descriptive Analysis and Multiple Regression. The analysis findings is benefits of unit trust, the most significance factor that affect and most positive relationship with the level of Malay awareness. The conclusion and recommendations revealed the results of the findings which include the analysis of the factors studied. The recommendations are based on the conclusion of the study.